2015
DOI: 10.1186/s13046-015-0183-0
|View full text |Cite
|
Sign up to set email alerts
|

Metformin can block precancerous progression to invasive tumors of bladder through inhibiting STAT3-mediated signaling pathways

Abstract: BackgroundMetformin is the first line of oral antidiabetic drug in the biguanide class for treatment of type 2 diabetes. Increasing evidence has suggested that it is a potential anti-tumor drug. However, the mechanisms underlying inhibiting tumor development remain elusive, especially in bladder tumors.MethodsT24 and J82 cell lines were used as an in vitro model, and 24 female SD rats were used to build an N-methyl-N-nitrosourea (MNU)-induced orthotopic rat bladder cancer model. Transfection of lentivirus-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…It was already known that metformin impairs the proliferation of several tumor cells Salani et al, 2013;W€ urth et al, 2013;Barbieri et al, 2015;Cheng and Lanza-Jacoby, 2015;Pan et al, 2015] and this ability was confirmed by the data obtained by our group (Fig. 8).…”
Section: Discussionsupporting
confidence: 88%
“…It was already known that metformin impairs the proliferation of several tumor cells Salani et al, 2013;W€ urth et al, 2013;Barbieri et al, 2015;Cheng and Lanza-Jacoby, 2015;Pan et al, 2015] and this ability was confirmed by the data obtained by our group (Fig. 8).…”
Section: Discussionsupporting
confidence: 88%
“…Several risk factors, such as smoking, paint and human papillomavirus infection, have been involved in carcinogenesis of urinary bladder [4]. A recent meta-analysis of 15 cohort studies concluded that pre obese has a significantly increased risk of bladder cancer by 7%, while obesity increases the risk of bladder cancer by approximately 10%.…”
Section: Introductionmentioning
confidence: 99%
“…All animals received care in compliance with the guidelines outlined in the Guide for the Care and Use of Laboratory Animals, and all procedures were approved by the Animal Care and Use Committee of Jilin University. As depicted in Scheme 1 , the orthotopic BC was induced by intravesical instillation of MNU every other week for a total of eight weeks 26. To confirm whether the BC was successfully induced or not, at the end of the intravesical instillation of MNU, the histopathological examination was performed.…”
Section: Resultsmentioning
confidence: 99%